697 The muscle strength of the hip joint can be used as a criterion of quality rehabilitation patients after total hip arthroplasty (Balneo and PRM Research Journal, 2024)
The primary aim of this study is to evaluate the efficacy of rehabilitation following total hip arthroplasty (THA) through the assessment of hip joint mobility parameters, namely abduction, extension, and flexion, at 2, 4, and 6 weeks post-surgery. These evaluations coincide with the implementation of rehabilitation exercises recommended by the physiotherapist. The study intends to analyze the progression of hip mobility during these specific time intervals in conjunction with the prescribed rehabilitation program. By examining the relationship between the performed exercises and the observed improvements in hip mobility, the research aims to provide valuable insights into the effectiveness of the rehabilitation protocol in facilitating post-THA rehabilitation. Material and method: The evaluation of hip joint mobility encompassed measurements of abduction, extension, and flexion utilizing a "Active Force 2" digital dynamometer. In tandem, the functional assessment of patients' health status was conducted through the utilization of the WOMAC index (Western Ontario and McMaster Universities Osteoarthritis Index). Results: The experimental data acquired in the measurement joint mobility during abduction, extension and flexion at 2, 4 and 6 weeks of exercises performed after THA are presented. Pain: mean score decreased from 3.08 to 1.18 (38.31% improvement); physical difficulties: mean score decreased from 3.10 to 1.01 (32.25% improvement) and joint stiffness: mean score decreased from 3.41 to 0.65 (19.06% improvement). These findings highlight the effectiveness of the recovery exercises in reducing pain, improving physical function, and decreasing joint stiffness post-THA. Conclusions: Our research emphasizes the essential contri-bution of physiotherapists to achieving positive outcomes for patients post-THA surgery. Through a personalized physiotherapy regimen administered during follow-up appointments, patients undergoing THA exhibited notable functional improvements. The study's results high-light the efficacy of this approach in alleviating discomfort, expediting recovery, and enhancing patients' overall quality of life, enabling a smoother transition back to normal daily activities.